Hedge Funds and Analyst Optimism - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2010)
We find that analysts are more likely to issue favorable recommendations for stocks predominantly owned hedge funds. Moreover, these optimistic recommendations translate into poorer stock performance over the next three to six months. Hedge funds take advantage of these flattering reports by concurrently offloading their stock holdings. Our results suggest that analysts are reluctant to downgrade stocks held by their most important clients.